Development and clinical application of a endonuclease restriction real-time loop-mediated isothermal amplification (ERT-LAMP) assay for rapid detection of Haemophilus influenzae - Cheng, Jinzhi; Zhou, Yuhong; Zhao, Xue; Lu, Jingrun; Wu, Jiahong; Wang, Yu (Frontiers in Microbiology, 2022)
Haemophilus influenzae (H.influenzae), is a major human pathogen, which can cause a series of diseases in children and adults, such as pneumonia, bacteremia, meningitis and so on. At present, although there are many detection methods, they can not meet the requirements of early diagnosis strategy. Therefore, rapid, sensitive and specific diagnostic strategies are very important for the prevention and control of H.influenzae infection. In this study, A novel detection method was reported based on the loop-mediated isothermal amplification (LAMP), combined with restriction endonuclease digestion and real-time fluorescence detection applied it for the diagnosis of H.influenzae (H.influenzae-ERT-LAMP). H.influenzae-ERT-LAMP integrates LAMP amplification, restriction endonuclease cleavage and real-time fluorescence detection into one-pot reaction, and facilitates the diagnosis of H.influenzae for only 40 min. A set of H.influenzae-ERT-LAMP primers was designed based on the outer membrane protein (OMP) P6 gene of H.influenzae. The limit of detection (LoD) of H.influenzae-ERT-LAMP assay was 40fg of each genomic DNA per reaction, and no positive results were obtained from non-H.influenzae templates. In order to evaluate the practicability of H.influenzae-ERT-LAMP assay in clinical sample detection, collected 30 sputum samples of patients who were suspected of infecting with H. influenzae, the H.influenzae-ERT-LAMP results showed completely in accordance with LAMP-LFB, and PCR. Briefly, the H.influenzae-ERT-LAMP assay offers a rapid, reliable and sensitive detection of H.influenzae, which can be used as a potential screening tool for H.influenzae in clinical and basic laboratory environment.